aaB: Strophic Design and Cognition - Cohen, Rip (Cognitive philology, 2013)
This paper assesses the Galician-Portuguese aaB forms using philological analysis, the concept of cognitive “chunk” (Miller 1956), a theory of expectation (Huron 2006), and a link between metrical asymmetry and working memory (Fabb, forthcoming). It argues that aaB corresponds to the needs and limits of cognition. With three to six cognitive chunks, aaB would have satisfied a set of metrical, para-metrical, verbal and semantic-pragmatic predictions and provided positive limbic evaluations. The whole strophe would have served as a unit of memory thanks to these energy saving operators.